The art of teaching : best practices from a master educator - Allitt, Patrick N. (Chantilly, VA : Great Courses, 2010)
One of the most dynamic and innovative Great Courses we've ever produced, The Art of Teaching is designed to help you achieve new levels of success as a teacher. These 24 lectures will help you develop and enhance your teaching style; provide you with invaluable methods, tools, and advice for handling all manner of teaching scenarios; and open your eyes to how other teachers{u2014}and their students{u2014}think about and approach this life-changing profession.
Lecture 1. Successful teaching --
lecture 2. Broad range of learners --
lecture 3. Starting out right --
lecture 4. The teacher's persona --
lecture 5. Planning the work --
lecture 6. The teacher-student relationship --
lecture 7. Dynamic lecturing --
lecture 8. Teaching with PowerPoint --
lecture 9. Demonstrations, old and new --
lecture 10. Teaching the critical skills --
lecture 11. Engaging with discussion, Part 1 --
lecture 12. Engaging with discussion, Part 2 Lecture 13. Cogent thinking and effective writing --
lecture 14. Teaching revision and editing --
lecture 15. Coaching students on presentation skills --
lecture 16. One-on-one teaching --
lecture 17. Learner's perspective --
lecture 18. Exams, evaluation, and feedback --
lecture 19. Maintaining your enthusiasm --
lecture 20. Managing the challenges of teaching --
lecture 21. Creativity and innovation --
lecture 22. Myths, lies, and half-truths --
lecture 23. The anatomy of a great teacher --
lecture 24. Teaching and civilization.
Includes bibliographical references.
Complimentary copy fromPDC
Amazon.com
Keywords: Teaching; Effective teaching; Teacher effectiveness